Як запобігати війнам? - Костенко, О.М. (Вісник НАН України, 2024)
Сьогодні в контексті воєнної агресії РФ проти України все більш очевидною стає істина: «краще запобігти війні, ніж потім воювати». Академічна наука не може залишатися осторонь проблеми гарантування безпеки людства, і наукова спільнота має виконати миротворчу місію — використати свій потенціал для пошуку шляхів вирішення глобального завдання із запобігання війнам. На основі власних досліджень автор робить, зокрема, такі висновки: виявлення з використанням методології соціального натуралізму причин, що породжують воєнну агресію, дозволяє прогнозувати ймовірність війни; здатність виявляти причини воєн відкриває можливості для запобігання їм; основним фактором запобігання воєнній агресії є культивування соціальної культури громадян, протидія їхній соціопатизації, яка й формує у людей «волю до війни» і зрештою спричиняє воєнну агресію. Today, in the context of Russia’s military aggression against Ukraine, the truth is becoming more and more obvious: “it is better to prevent war than to fight it”. Academic science cannot stay aloof from the problem of ensuring the security of humanity, and the scientific community must fulfill a peacekeeping mission — to use its potential to find ways to solve the global task of preventing wars. Based on his own research, the author draws the following conclusions: identifying the causes of military aggression using the methodology of social naturalism allows predicting the likelihood of war; the ability to identify the causes of wars opens up opportunities for preventing them; the main factor in preventing military aggression is the cultivation of social culture of citizens, counteracting their sociopathization, which forms people’s “will to war” and ultimately causes military aggression.